ETIKA PROFESI GURU DALAM PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) UNTUK PENYUSUNAN MATERI PEMBELAJARAN DI ERA DIGITAL - Khoiril, Nurussyifa; Husniya, Taiba; Muna, Nila Nilnal; Khasanah, Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Artificial Intelligence (AI) provides practical support for teachers in developing learning materials, yet it also raises challenges related to professional ethics. This study aims to analyze the importance of teachers’ professional ethics in the use of AI to ensure that reflective roles and pedagogical quality are maintained in the digital era. The research employs a qualitative approach through a literature review, using scientific journals, books, and educational policy documents as data sources. The findings indicate that uncontrolled use of AI may reduce teachers’ creativity, weaken independent analytical skills, and increase the risk of academic misuse. Therefore, AI should be positioned as a supporting tool rather than a replacement for the teacher’s primary role. These findings highlight the need to strengthen and adapt teachers’ professional ethical codes so that the use of technology remains aligned with moral and professional responsibilities, while maintaining a balance between digital innovation and human values in meaningful education.